LINK STABLE INTELLIGENT CACHING MULTIPATH AND MULTICAST ROUTING PROTOCOL FOR WSN - Damaraju, Padmaleela; Shayee, M. Sesha (International Journal of Computer Sciences and Engineering, 2025)
Quality of Services is an important aspect in Wireless Adhoc network, where nodes are organized with reduced resources like low energy and low bandwidth due to the lack of network infrastructure. There are various QOS aware routing protocol presented to improve the link quality to enhance the WSN quality of services, but most of these protocols were limited to efficient routing and to minimizing the overhead. Moreover many of these protocols suffer from design issues which makes quality of service ,a challenging research task due to lack of efficient routing protocols . In this protocol we propose a new multipath, multicast routing protocol that addresses the issue of route congestion .In this protocol we propose a Link Stable Intelligent Caching Multipath and Multicast Routing protocol for WSN by adopting particle swarm optimization technique to identify the optimal route and employed intelligent caching to minimize route congestion and to improve the load balancing